Improving the fast-charging capability of NbWO-based Li-ion batteries - Yaqing Guo; Chi Guo; Penghui Li; Wenjun Song; Weiyuan Huang; Junxin Yan; Xiaobin Liao; Kun He; Wuxin Sha; Xuemei Zeng; Xinyue Tang; QingQing Ren; et al. (Nature Communications)
Abstract The discovery of Nb-W-O materials years ago marks the milestone of charging a lithium-ion battery in minutes. Nevertheless, for many applications, charging lithium-ion battery within one minute is urgently demanded, the bottleneck of which largely lies in the lack of fundamental understanding of Li+ storage mechanisms in these materials. Herein, by visualizing Li+ intercalated into representative Nb16W5O55, we find that the fast-charging nature of such material originates from an interesting rate-dependent lattice relaxation process associated with the Jahn-Teller effect. Furthermore, in situ electron microscopy further reveals a directional, [010]-preferred Li+ transport mechanism in Nb16W5O55 crystals being the “bottleneck” toward fast charging that deprives the entry of any desolvated Li+ through the prevailing non-(010) surfaces. Hence, we propose a machine learning-assisted interface engineering strategy to swiftly collect desolvated Li+ and relocate them to (010) surfaces for their fast intercalation. As a result, a capacity of ≈ 116 mAh g−1 (68.5% of the theoretical capacity) at 80 C (45 s) is achieved when coupled with a Li negative electrode.